Overseas R&D by Multinationals in Foreign Centers of Excellence - Gunnar Fors; Mario Zejan (The Research Institute of Industrial Economics (IUI), 1996)
This paper examines the determinants of overseas R&D by Swedish multinationals. Our empirical results indicate that the location of R&D abroad to a large extent is motivated by the need to adapt products and processes to conditions in the foreign markets where the firms operate. However, we also find that the MNEs tend to locate their R&D in host countries which are relatively specialized technologically in the firms' own areas. This finding may suggest that one additional motive to locating R&D abroad is to gain access to knowledge in foreign 'centers of excellence' and benefit from localized spillovers.
Keywords: F23; O32; 330; Overseas R&D; Technology Sourcing; Multinationals; Industrieforschung; Multinationales Unternehmen; Schweden